2020
DOI: 10.1097/aud.0000000000000836
|View full text |Cite
|
Sign up to set email alerts
|

Cortical fNIRS Responses Can Be Better Explained by Loudness Percept than Sound Intensity

Abstract: Objectives: Functional near-infrared spectroscopy (fNIRS) is a brain imaging technique particularly suitable for hearing studies. However, the nature of fNIRS responses to auditory stimuli presented at different stimulus intensities is not well understood. In this study, we investigated whether fNIRS response amplitude was better predicted by stimulus properties (intensity) or individually perceived attributes (loudness). Design: Twenty-two young adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
7
22
1
Order By: Relevance
“…As expected, applying the short-channel method to remove systemic components resulted in a substantial improvement in the detection rate. 41 , 51 53 Although it is common to use just the first or second PCs as regressors, 2 we observed that including all components resulted in the best performance, consistent with Huppert. 74 Including either all PCA components, the mean, or all individual short channels simplifies analysis as these approaches do not require a specific selection criterion, making them easy to implement, describe, and replicate.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As expected, applying the short-channel method to remove systemic components resulted in a substantial improvement in the detection rate. 41 , 51 53 Although it is common to use just the first or second PCs as regressors, 2 we observed that including all components resulted in the best performance, consistent with Huppert. 74 Including either all PCA components, the mean, or all individual short channels simplifies analysis as these approaches do not require a specific selection criterion, making them easy to implement, describe, and replicate.…”
Section: Resultssupporting
confidence: 84%
“…A primary use has been the investigation of cortical processing of physical qualities of sound, such as intensity, amplitude and frequency modulations, and auditory-spatial cues. 2 4 fNIRS has also been employed to evaluate the perceptual qualities of speech and listening effort and language development in normal-hearing and hearing-impaired populations. 5 14 Research questions relating to the development of auditory cortical function 15 and cortical reorganization following impaired sensory input and subsequent rehabilitation 16 , 17 have been investigated using fNIRS, as have outcomes related to cochlear implantation 5 and auditory pathologies such as tinnitus.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, applying the short-channel method to remove systemic components resulted in a substantial improvement to the detection rate (Santosa et al, 2020;Scholkmann et al, 2014;Tak and Ye, 2014;Wyser et al, 2020). Although it is common to use just the first or second principal components as regressors (Weder et al, 2020), we observed that including all components resulted in the best performance, consistent with Santosa et al (2020).…”
Section: Effect Of Short Channel Regression On Detection Of Auditory supporting
confidence: 91%
“…A primary use has been the investigation of cortical processing of physical qualities of sound, such as intensity, and amplitude and frequency modulations, and auditory-spatial cues (Weder et al, 2020;Weder et al, 2018;Zhang et al, 2018). fNIRS has also been employed to evaluate the perceptual qualities of speech and listening effort, as well as language development in normal-hearing and hearing-impaired populations (Anderson et al, 2019;Lawrence et al, 2018;Mushtaq et al, 2019;Pollonini et al, 2014;Rovetti et al, 2019;Rowland et al, 2018;Sevy et al, 2010;Wiggins et al, 2016b;Wijayasiri et al, 2017;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A good knowledge of the interrelationship between stimulus parameters and the functional imaging signal response is critical for designing the experimental protocol and interpreting cortical activation. Initially, one should carefully consider auditory stimulus properties, which include intensity, frequency modulation, single stimulus duration, and spatial cues (Bauernfeind et al, 2018;Weder et al, 2018Weder et al, , 2020Zhang et al, 2018). Then, stimulation parameters should be optimally chosen, including stimulus presentation rate (Binder et al, 1994), interstimulus intervals, and block stimulation durations (Robson et al, 1998;Hu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%